Rancang Bangun Dan Pengujian Alat Pengering Solar Dryer Sederhana (Constructing and Experiment of Simple Solar Dryer) - Frets Jonas Rieuwpassa; Stevy Imelda Murniati Wodi; Eko Cahyono; Rolando Pangumpia (Universitas Sriwijaya, 2019)
Solar dryer is a device that use solar energy to try substances. Using a solar dryer is more hygiene than drying directly into the sun. This experiment aims to construct a solar dryer device and to examine product water content. There are some steps in this experiment which are constructing a solar dryer device and examination of the product water content of two different solar device construction. Products that examined are mackerel tuna dried with salt and without salt. Water content examination is established every 4 hours and 12 hours. All data are examined descriptively. Results showed that temperature in device type 1 are between 40-45 0C dan device type 2 are between 44-45 0C. Results for water content in salted dry fish showed a score of 37.99% in device type 1 and 30.27% in device type 2. For water content in non-salted dry fish showed a score of 38.4% in device type 1 and 27.35% in device type 2. Base on this it can be concluded that device type 2 able to lower water content in products better than device type 1.